Alister McGrath. Christianity’s Dangerous Idea: The Protestant Revolution – A History from the Sixteenth Century to the Twenty-First = Alister MAkgrAt. NebezpečNAidejachrystyjaNstvA. pRotestantsʹkaRevoljucija: istoRijavidšistnadcjatohododvadcjatʹpeRšohostolittja - Mokiyenko, Mikhailo (Bogoslovskie razmyšlenija, 2017)
Book review: Alister McGrath. Christianity’s Dangerous Idea: The Protestant Revolution - A History from the Sixteenth Century to the Twenty-First. - 656 с. ISBN 978-966-378-548-6The 500th anniversary of the Reformation gave rise to a surge in publications of various kinds and quality. Against this background Alister McGrath’s book really stands out: the Oxford professor studies the history of the Protestant revolution from 16th to 21st centuries. The book was published in 2006; the Ukrainian translation ("Dukh i litera" publishing house) appeared in 2017 through the effort of the Resource and Research Center of the Euro-Asian Accrediting Association of evangelical schools.